Performance of geometrical effect in wavelength filtrate detection using 10gbps data rate for free space optical communication system - M.F Talib; Anuar M.S; C.B.M. Rashidi (Institute of Advanced Engineering and Science, 2019)
In this paper, the analysis of comparison between proposed detection called as Wavelength Filtrate Detection with existing detection have been analyzed to determine the best system performance in term of power received and bit error rate (BER). The analysis focus on the geometrical effect of aperture receiver and beam divergence. The performance of Free Space Optics is validated through simulation analysis using parameter 10Gbps data rate and in 14dB/km atmospheric attenuation. This analysis shows that Wavelength Filtrate Detection increase the power received of 6dBm and improve the absolute value of error rate 10-9 in acceptable threshold required by (ITR-U) as much as 50% compare to others existing detection